2010
DOI: 10.1002/cncr.25676
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin‐3 (SIRT3), a novel potential therapeutic target for oral cancer

Abstract: BACKGROUND Several sirtuin family members (SIRT1-7), evolutionarily conserved NAD-dependant deacetylases, play an important role in carcinogenesis. However, their role in oral cancer has not yet been investigated. Therefore, the aim of this study was to investigate whether sirtuins play a role in oral cancer carcinogenesis. METHODS We examined the expression levels of all sirtuins in several oral squamous cell carcinoma (OSCC) cell lines compared to normal human oral keratinocytes, and found SIRT3 was highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
184
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(196 citation statements)
references
References 38 publications
8
184
1
3
Order By: Relevance
“…16,17 Accumulating studies demonstrated that many types of cancers exhibited aberrant expression or deletion of SIRT3. [18][19][20] However, the function of SIRT3 in HCC development remains enigmatic. In our study, significantly reduced expression of SIRT3 mRNA and protein were observed in HCC tissues, in comparison with normal adjacent tissues by qRT-PCR, IHC, and Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Accumulating studies demonstrated that many types of cancers exhibited aberrant expression or deletion of SIRT3. [18][19][20] However, the function of SIRT3 in HCC development remains enigmatic. In our study, significantly reduced expression of SIRT3 mRNA and protein were observed in HCC tissues, in comparison with normal adjacent tissues by qRT-PCR, IHC, and Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic properties of SIRT3 are attributed to its actions in stimulation of proliferation, resistance to oxidative stress, and suppression of apoptosis. SIRT3 could play an oncogenic role in a spectrum of cancers including oral squamous cell carcinoma [58], breast cancer [59], esophageal cancer [60], gastric cancer [61], colorectal cancer [62], and melanoma cell lines [63].…”
Section: Changes In Sirtuin 3 Expression In Carcinogenesismentioning
confidence: 99%
“…Авторам этой работы удалось доказать, что эффект СГК опосредуется реактивацией экспрессии ряда тумор-супрессорных микроРНК, в частности miR-107 и miR-138. Ранее было показано, что miR-107 существенно снижала туморогенность клеток ОГШ за счет взаимодей- [95]. Экспрессия сиртуина-3 в опухолевых клетках оказалась существенно выше, чем в клетках нормального эпителия, а эксперимен-тальная инактивация этой молекулы ингибировала пролиферацию и злокачественный потенциал опухо-левых клеток.…”
Section: Introductionunclassified
“…Кроме этого, снижение уровня сиртуи-на-3 повышало чувствительность опухолевых клеток к радио-и химиотерапии. Таким образом, использо-вание сиртуина-3 в качестве терапевтической мишени у пациентов с ОГШ и высоким уровнем экспрессии этого белка может иметь самостоятельный эффект или использоваться в качестве адъювантной терапии радио-и химиорезистентных опухолей [95]. Авторами цитируемой работы был синтезирован ингибитор сир-туина-3 -LC-0296 -и исследован эффект этого веще-ства на пролиферативную активность клеток плоско-клеточного рака слизистой оболочки полости рта.…”
Section: Introductionunclassified
See 1 more Smart Citation